(untitled) (REVISTA NODO, 2009)
This article is the product of a monographic study that depicts the results of an ethnographic examination conducted in Santiago de Cali’s fifth street South during the course of a few months, which purpose was knowing, interacting and analyzing a distinguishing phenomenon occurring in the public space: the South Chaplin’s performance. The power of the representation as well as the comprehensible acting of the character allowed the researchers to recognize the dynamics that Richard Senett and Erving Goffman have theorized around observation and urban micro-sociology.